Implementasi Permendagri Nomor 18 Tahun 2018 Pasal 7 Ayat 5 Dalam Melaksanakan Pemberdayaan Masyarakat Desa - Akbar Mukti Laksana; Almisar Hamid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Community Empowerment Institutions are village government development partners to create prosperity for village communities. This task is stated in the Minister of Home Affairs Regulation Number 18 of 2018 concerning Village Community Institutions and Village Traditional Institutions, Article 7 Paragraph 5. However, what has happened is that the implementation of this policy has not been carried out well, as evidenced by the phenomenon of the community not understanding the duties of Community Empowerment Institutions which ultimately results in misappropriation of duties that are not in accordance with the guidelines. The aim of this research is to determine the implementation of Minister of Home Affairs Regulation Number 18 of 2018 Article 7 Paragraph 5. This research uses a qualitative descriptive method by collecting data through interviews and documentation. Determining informants used snowball sampling with five informants and data analysis using the Miles & Huberman model. This research resulted in the non-implementation of Minister of Home Affairs Regulation Number 18 of 2018 regarding the duties of Community Empowerment Institutions, as evidenced by the implementer's understanding of policies, quality of human resources, socio-economic and political conditions, communication and coordination, institutional characteristics, and non-compliance of Minister of Home Affairs Regulations with Regional Regulations.